2016
DOI: 10.1039/c6cc02387h
|View full text |Cite
|
Sign up to set email alerts
|

Maleic anhydride proton sponge as a novel MALDI matrix for the visualization of small molecules (<250 m/z) in brain tumors by routine MALDI ToF imaging mass spectrometry

Abstract: A novel vacuum stable proton sponge, 4-maleicanhydridoproton sponge (MAPS), was prepared and applied as the matrix in Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Imaging (MALDI-MSI) of an aggressive brain tumor tissue (glioblastoma multiforme). Ionic maps of lactate, 2-hydroxyglutarate and chloride anions (m/z 89, 147, 35, respectively) were obtained using a routine MALDI ToF mass spectrometer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…The use of classical matrices for the MALDI‐MSI detection of low molecular weight compounds leads to strong background signals in the low mass range of the spectrum due to the ionization of the matrix, related clustering processes, and because of susceptibility to in‐source fragmentation of small molecules . The MAPS matrix is suitable for the MALDI‐MSI analysis of small molecules lower than 250 Da . In the study of Giampà et al, it is shown by scanning electron microscope (SEM) images that MAPS matrix produces a thin film when applied on tissues, rather than a crystalline structure as, eg, in case of DHB .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of classical matrices for the MALDI‐MSI detection of low molecular weight compounds leads to strong background signals in the low mass range of the spectrum due to the ionization of the matrix, related clustering processes, and because of susceptibility to in‐source fragmentation of small molecules . The MAPS matrix is suitable for the MALDI‐MSI analysis of small molecules lower than 250 Da . In the study of Giampà et al, it is shown by scanning electron microscope (SEM) images that MAPS matrix produces a thin film when applied on tissues, rather than a crystalline structure as, eg, in case of DHB .…”
Section: Discussionmentioning
confidence: 99%
“…The MAPS matrix is suitable for the MALDI‐MSI analysis of small molecules lower than 250 Da . In the study of Giampà et al, it is shown by scanning electron microscope (SEM) images that MAPS matrix produces a thin film when applied on tissues, rather than a crystalline structure as, eg, in case of DHB . Apparently, the lack of visible crystals does not hinder the adequate ionization of metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations